Eigenvectors of Open Bazhanov-Stroganov Quantum Chain - Iorgov, N. (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
In this contribution we give an explicit formula for the eigenvectors of Hamiltonians of open Bazhanov-Stroganov quantum chain. The Hamiltonians of this quantum chain is defined by the generation polynomial An(λ) which is upper-left matrix element of monodromy matrix built from the cyclic L-operators. The formulas for the eigenvectors are derived using iterative procedure by Kharchev and Lebedev and given in terms of wp(s)-function which is a root of unity analogue of Γq-function.